Treatment of rigid post-traumatic thoracolumbar kyphosis by a novel technique of spinal joints release - Wang, Qing; Tang, Chao; Wang, GaoJu; Li, GuangZhou; Zhong, DeJun; Wang, Song; Ma, Fei (Journal of orthopaedic surgery and research, 2023)
The purpose of this study was to evaluate the feasibility of a novel technique named spinal joints release (SJR) and observe its efficacy in treating rigid post-traumatic thoracolumbar kyphosis (RPTK). RPTK patients who were treated by SJR with facet resection, limited laminotomy, clearance of the intervertebral space, and release of the anterior longitudinal ligament through the intervertebral foramen and disc of injury segment from August 2015 to August 2021 were reviewed. Intervertebral space release, internal fixation segment, operation time, and intraoperative blood loss were recorded. The intraoperative, postoperative, and final follow-up complications were observed. An improvement in the VAS score and ODI index was observed. Spinal cord functional recovery was evaluated by American Spinal Injury Association Impairment Scale (AIS). Improvement of local kyphosis (Cobb angle) was evaluated by radiography. Forty-three patients were successfully treated by the SJR surgical technique. Open-wedge anterior intervertebral disc space was performed in 31 cases, and repeated release and dissection of the anterior longitudinal ligament and callus were performed in 12 cases. There was no lateral annulus fibrosis release in 11 cases, the anterior half release of lateral annulus fibrosis in 27 cases, and complete release in five cases. There were five cases of screw placement failure in one or two side pedicles of the injured vertebrae due to excessive resection of the facets and improper pre-bending of the rod. Sagittal displacement occurred in four cases at the released segment due to the complete release of bilateral lateral annulus fibrosus. Autologous granular bone + Cage was implanted in 32 cases, and autologous granular bone was implanted in 11 cases. There were no serious complications. The average operation time was 224 ± 31 min, and intraoperative blood loss was 450 ± 225 mL. All the patients were followed up with an average of 26 ± 8.5 months. The VAS scores and ODI index improved significantly at the final follow-up. All of the 17 patients with incomplete spinal cord injury achieved more than one grade of neurological recovery at the final follow-up. An 87% correction rate of kyphosis was achieved and maintained, with the Cobb angle decreasing from 27.7° preoperatively to 5.4° at the final follow-up. Posterior SJR surgery for patients with RPTK has the advantages of less trauma and less blood loss, and kyphosis correction is satisfactory.